Dr. Ahmad Irfan creates iLocSolat Mobile App for the next-generation prayer time calculation - Safriza, Baharuddin (UMPSA, 2023)
GAMBANG, 10 October 2023 - Dr. Ahmad Irfan Ikmal Hisham, a Senior Lecturer at the Center for Human Sciences (PSK), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), has developed the iLocSolat Enhanced Geotagging Based Prayer Time Smart Application, which is a next-generation mobile application for prayer time calculation.